Pandangan Ali Jum‘Ah Mengenai Riba dan Tantangannya Terhadap Konsep Mata Uang Fiat - Muhamad Mushollih Abdul Gofar; Nur Arfiyah Febriani; Syahrullah Iskandar (International Journal Labs, 2026)
The issue of usury and the use of fiat currency is a crucial debate in contemporary Islamic economic discourse. One figure who has paid serious attention to this issue is Ali Jum'ah, an Egyptian cleric and former Mufti of al-Diyâr al-Mi?riyyah. This article aims to analyze Ali Jum'ah's views on verses about usury and his conceptual challenges to the existence and legitimacy of fiat currency in the modern monetary system. This research uses a qualitative method with a content analysis approach to Ali Jum'ah's studies delivered through his official YouTube channel. The data were analyzed by examining the interpretation arguments, the Islamic jurisprudence approach, and the socio-economic context underlying his views. The results show that Ali Jum'ah views usury as a practice expressly prohibited in the Qur'an, but its application in the modern economic system requires a contextual understanding. He emphasized that fiat currencies cannot be automatically categorized as usurious instruments as long as they do not contain elements of oppression, exploitation, and injustice. This view demonstrates an effort to reconstruct an understanding of usury that is adaptive to contemporary economic realities without ignoring sharia principles. This research is expected to enrich the body of Islamic economic studies, particularly in responding to the dynamics of the modern monetary system.